Diuretic and Natriuretic Effects of Dipeptidyl Peptidase-4 Inhibitor Teneligliptin: The Contribution of Glucagon-like Peptide-1. Issue 2 (August 2015) - Moroi, Masao; Kubota, Tetsuya
Abstract : Abstract: Glucagon-like peptide-1 receptor (GLP-1R) agonists and dipeptidyl peptidase-4 (DPP-4) inhibitors are antidiabetic agents; however, their mechanisms of action are different. GLP-1R and DPP-4 are also expressed in the renal proximal tubular brush border, where they regulate Na + reabsorption. We investigated whether the DPP-4 inhibitor, teneligliptin, has diuretic and natriuretic effects and whether these are associated with the stimulation of the GLP-1R in rats. Oral administration of teneligliptin resulted in a reduction of plasma DPP-4 activity over 6 hours, as well as an induction of diuresis and natriuresis. Although teneligliptin did not change the increase in blood glucose levels by glucose loading, percentage of urine volume and Na + /K + ratio with teneligliptin to vehicle were augmented by glucose loading. Peak levels of plasma GLP-1 did not change after oral administration of teneligliptin when glucose was not loaded but increased at least 2-fold with glucose loading. Furthermore, the natriuretic effect of teneligliptin was inhibited by the GLP-1R antagonist, exendin9-39, whereas the diuresis was not affected. These results suggest that the mechanism of natriuresis was different from that of diuresis, and the natriuresis is associated with the stimulation of GLP-1R. There may be mechanistic differences in DPP-4 inhibition between diuresis and natriuresis.